Superworm (Zophobas morio) breeding for papaya stem waste management - Nina Lisanty; Nugraheni Hadiyanti; Moch. Agus Suryo Wibowo; Nanang Aji Saputro; Nixie Azalia Whintisna; Rafelda Dias Nurfitri (Journal of Community Service and Empowerment, 2023)
Boyolangu District is a famous papaya-producing area and the largest in Tulungagung Regency. The local papaya farming community is active in farming. They succeeded in producing approximately 10 tons of papaya in 2020. This number has decreased by more than half from the previous year in 2019. This is inseparable from the impact of the COVID-19 pandemic. In addition, the community complaint about a large amount of papaya stem waste after harvest. Waste management is a separate problem for farmers. Not to mention the added problem of the low price of papaya per kilogram. Therefore, a community service program aims to overcome the target community's problems with superworm (Zophobas morio) breeding education and training. The activity conducted by the team of the Faculty of Agriculture, University of Kadiri empowering the papaya farming community in Boyolangu District, Tulungagung Regency to manage papaya stem waste as an alternative feed for superworm breeding. Farmers were invited to breed superworm as their additional income and improve the standard of living of the family. This activity mainly focused on the introduction and training of superworm breeding. The activity was beneficial for the social, economic, and environmental life of the target community.